Penentuan Harga Air Tanah untuk Irigasi Berkelanjutan di Kabupaten Jembrana - WIRAWAN, IDA BAGUS MADE; SUDARMA, I MADE; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Determination of Groundwater Prices for Sustainable Irrigation in Jembrana Regency Subak Babakan Yehkuning is relatively new in obtaining Groundwater Irrigation Network, with the code YKN-127 in 2014. This study aims to determine the cost components and water prices that reflect the value of water use in a sustainable manner. The method used in this research is quantitative calculation. The total water discharge from YKN-127 for three planting seasons in September 2015 until August 2016 consecutively was 83,647.01 m3. This amount was derived from the total life of the pump for 2,733 hours, with a discharge 8.5 liters/second. The commodities cultivated in three planting seasons were rice for two times and secondary crop (corn and soybean). Since the availability of ground water has a limited amount, it is important to note that the amount of water use should be less than the availabilities. The concept of sustainable value in the use of water is consisted of the total cost of supply, opportunity costs, and externalities costs. The results showed that the water price reflecting the sustainable water use value for irrigation at YKN-127 was Rp 3,933.91/m3, which consisted of a full supply cost 65.9% (Rp 2,592.42/m3), an opportunity cost 27.9% (Rp 1,099.43/m3), and depletion premium 6.2% (Rp 242.06/m3). This result is almost three times the operational and maintenance costs that farmers usually pay for Rp 1,633.99/m3. This price describes the value that must be paid as an effort to maintain the development of irrigated agriculture sector and ground water resources in order to remain sustainable in Jembrana, Bali Province.